Comparison of phenotypic tests for detecting penicillin G resistance with presence of blaZ gene in Staphylococcus aureus isolated from bovine intramammary infections - Russi, Norma B.; Maito, Julia; Dieser, Silvana Andrea; Renna, Maria Sol; Signorini, Marcelo; Camussone, Cecilia; Neder, Veronica Elizabeth; Pol, Martín; Tirante, Liliana; Odierno, Liliana Mónica; Calvinho, Luis Fernando (2018)
Few studies have described the relationship between genotypic and phenotypic methods for detecting penicillin resistance in Staphylococcus aureus isolated from bovine intramammary infection (IMI). Six phenotypic methods for penicillinase detection were compared with a genotypic method testing the presence of the β-lactamase gene blaZ in Staph. aureus (n = 150) isolated from bovine IMI. Highest sensitivities and specificities were observed for disk diffusion (DD) (93 and 97·4%), minimum inhibitory concentration (MIC) (90·3 and 97·4%), Cefinase™ (85·9 and 97·4%) and Diatabs™ (85·7 and 98·7%). The estimated cut-off points estimated in the present study can be considered close to the ones indicated by CLSI (2013). The molecular detection of blaZ gene is the only method that may indicate the real or potential capacity of producing β-lactamase in Staph. aureus. Considering that from a clinical standpoint a false negative result from a phenotypic test is the most unfavourable situation, a combination of standard DD with Diatabs™ or Cefinase™ should be performed by routine mastitis laboratories to minimise false negative results.